Operasionalisasi Q.S. Ali Imran Ayat 14-19 Sebagai Standar Kerja Seorang Pengusaha Muslim - Ayuwan Nandani (MAGHZA, 2020)
This study examines the importance of operationalizing QS. Ä€li-ImrÄn verses 14-19 to form a Muslim entrepreneur figure who is following the description in the al-Qur'an. The figure of an entrepreneur who does not secularize, but rather an entrepreneur who can combine religious and business matters so that he can achieve happiness in the world and the hereafter. Therefore, a description of the interpretation of the verse is needed to obtain the essence, so that someone who wants to become an entrepreneur can use the operating system in running his business. From this research, it was found that every human being has the same opportunity. To be an entrepreneur. Being an entrepreneur is an easy matter, not as difficult as most people think. Easy here, of course, using the T & Cs that have been stipulated in the Koran, with the basic rundown of entrepreneurs as follows: 1) Seek Allah, 2) Prayer, 3) Repentance, 4) Involving Allah, 5) Amanah, 6) On-time 7) giving alms, and 8) extending the night. It is hoped that the results of this research can add to the wealth of knowledge in the field of Al-Qur'an and Tafsir and become a reference for someone who wants to become an entrepreneur without distinguishing anyone's background, social status, ability, and stability so that it can be understood that all can be entrepreneurs.